Radikalisme Islam dan Pergerakannya di Media Sosial - Nafi Muthohirin (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2015)
This article examines the rise of Islamic radicalism expressed through the virtual network (social media. Facebook, YouTube, Twitter, Tumbler, and other free ap- plication providers such as WhatsApp have become a spot for propaganda, recruit- ment, training, preparing, and calling for the establishment of Islamic Khilafa. Con- temporary strategy has been used by the “defenders of Islam” to influence Muslim society. In particular, the radical groups have actively used social media to target youth as the main users of social media. (netizen). This research focuses on Islamic fundamentalism, represented by radical groups such as Hizbut Tahrir Indonesia (HTI), Harakah Tarbiyah dan Jamaah Salafi